Interaction between two rows of localized adsorption sites in a 2D one-component plasma - Santangelo, C.D.; Blum, L. (Condensed Matter Physics, 2005)
We compute the free energy for two rows of localized adsorption sites
embedded in a two dimensional one-component plasma with neutralizing
background density ρ. The interaction energy between the adsorption sites
is repulsive. We also compute the average occupation number of the adsorption
sites and compare it to the result for a single row of sites. The
exact result indicates that the discretization does not induce charge asymmetry
and no attractive forces occur. Ми розраховуємо вільну енергію для двох рядів локалізованих
адсорбційних центрів, вставлених у двовимірну однокомпонентну
плазму з густиною нейтралізуючого фону ρ. Енергія взаємодії між
адсорбційними центрами є відштовхувальною. Ми також розраховуємо середнє число заповнення адсорбційних центрів і порівнюємо
його з результатом для одного ряду центрів. Точний результат
показує, що дискретизація не спричиняє зарядової асиметрії і не
виникають сили притягання.